MEASUREMENT AND ANALYSIS OF IMPACT OF SUPERVISION ON CONSTRUCTION LABOUR PRODUCTIVITY: A CASE STUDY OF NORTH-CENTRAL NIGERIA - ADAKOLE EDWIN , AGBO; CALISTUS , AYEGBA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Labour productivity is one crucial factor that directly affect profitability of construction contracting firms. Labour productivity is one of the most important issues being frequently discuss among construction firms, construction professionals and stake-holders in the construction industry as it has a significant impact on performance of all construction projects. This study focus on identifying supervision factors affecting labour productivity. The study analyse and quantify the impact of supervision on labour productivity in block laying and concrete activities in North-Central Nigeria. Questionnaire and direct site observation using time study was employed as data collection instrument. The data were analysed using relative importance index and regression model. The result of the analysis revealed that 7 factors were identified by Block layers and Concreters as factors under supervision group and significantly affect their productivity. The regression model result shows that in block laying, alteration of drawings and specifications during execution; Incompetent supervisors and late/unclear instructions were the top most factors having high negative impact (loss of productivity) of 0.745whr/m2; 0.637whr/m2 and 0.61whr/m2 respectively on labour productivity. In concreting, Inspection delay, supervision absentieesm, alteration of drawings and specifications during execution and incompetent supervisors were the 4 top most factors having high negative impact of 0.653whr/m2; 0.571whr/m2; 0.537whr/m2 and 0.518whr/m2 respectively on labour productivity. All the factors identified in this study have negative impact on labour productivity of the masonry trades considered in this study.